The family as a subject of law and economics: a balance of personal and entrepreneurial interests - Abugaliyeva, F.; Zhaskairat, M. (Bulletin of the Karaganda University “Law Series”, 2025)
The article considers the family as a multifaceted social institution that simultaneously performs the functions of a subject of law and economics. The author focuses on the dual nature of the family: on the one hand, it is a space of personal connections based on trust, love and mutual support, on the other — a carrier of property interests and a participant in economic activity. The article analyzes the legal subjectivity of the family, its limitations, as well as its economic role in the transformation of modern society. Special attention is paid to the problem of the balance between the personal and entrepreneurial dimensions of the family, the identification of contradictions between them and the search for possible mechanisms for their reconciliation. The importance of the family entrepreneurship as a form of realization of the economic function of the family and an important factor in the sustainability of society is emphasized.